2017
DOI: 10.2485/jhtb.26.268
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic ABCG2 and Podoplanin Expression in Oral Squamous Cell Carcinoma Correlates with Lymph Node Metastasis

Abstract: The cervical lymph node metastasis of Oral Squamous Cell Carcinoma (OSCC) has been considered to be the main causes of death. The aim of our study was to clarify the expression pattern of ABCG2 and podoplanin in OSCC tissues and corresponding cervical lymph node, and evaluate the diagnostic value of ABCG2 and podoplanin in OSCC for tumorigenesis, histological stage and clinical prognosis. ABCG2 showed a mixed membranous and cytoplasmic pattern of staining in specifi c regions of stratum corneum and the center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 19 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…The search strategy resulted in 721 records without duplicates. After full‐text reading, 58 studies were excluded (Appendix ) and 29 7,8,10,20‐45 were included (Figure 1). The same tissue samples were used in two included studies 23,29 (confirmed by personal communication, Dr Denise Oliveira, April 30, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The search strategy resulted in 721 records without duplicates. After full‐text reading, 58 studies were excluded (Appendix ) and 29 7,8,10,20‐45 were included (Figure 1). The same tissue samples were used in two included studies 23,29 (confirmed by personal communication, Dr Denise Oliveira, April 30, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2173 tumors were investigated across the 29 included studies. Males were usually more affected by OSCC than females 7,8,10,21‐31,33‐36,39‐42,44,45 . The participants' age ranged from 19 42 to 96 years, 36 with a mean age ranging from 50 39 to 69 years 22 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations